Applications of Advanced Metering Infrastructure in Electricity Distribution - World Bank (Washington, DC, 2013)
In the second half of the 1980s, several electricity companies in developed countries incorporated the automation of the reads of the consumption meters installed in their customers' premises. Adoption of that approach was driven in all the cases by the need to lower the significant costs of in-site reading, reflecting high labor costs in rich countries. There are several AMI options potentially viable for each of the automated meter reading (AMI) applications, covering a wide range in terms of technical and functional specifications of hardware and software. However, the technical and economic feasibility of a specific option crucially depends on the current operational and financial performance of the involved utilities, as well as on other key characteristics (institutional, regulatory, development of communications infrastructure) of the environment in which they operate. It is very clear that, in AMI, one size does not fit all. The applicability and options for applying AMI or smart meters technology to a variety of customer management issues commonly found in public service utilities, in particular in electricity distribution companies, are described and analyzed in this report.